High-intensity focused electromagnetic field – application in aesthetic medicine - Leonik, Szymon; Smoczok, Michał; Sazanów-Lubelski, Jakub; Bergler-Czop, Beata (Dermatology Review/Przegląd Dermatologiczny, 2022)
High-intensity focused electromagnetic field is one of the 5 non-invasive body shaping techniques approved by the U.S. Food and Drug Administration. There is a rising demand for these methods and their popularity is growing. The technology is based on electromagnetic stimulation that causes motor neurons to depolarize, and hence muscle contractions. So far, this method is the only one available that directly stimulates muscles. In this manuscript we analyse the current literature on the use of this method in aesthetic medicine. We present the procedure, the probable effects, a typical patient profile and the patients’ satisfaction after treatment.